Cultural Revolution and revolutionary culture - Russo, Alessandro, 1949- (Duke University Press, 2020)
"In CULTURAL REVOLUTION AND REVOLUTIONARY CULTURE, Alessandro Russo argues that the Cultural Revolution in China should be understood as a mass political experiment aimed at thoroughly reexamining the tenets of communism itself. Arguing that each political revolution must contend with that which preceded it, Russo contextualizes the Cultural Revolution within two overlapping historical periods: the span of communist ideology itself, beginning with the publication of the Communist Manifesto in 1848, and the political energy of the 1960s, in which a worldwide reconsideration of communism took place. Although the Cultural Revolution ultimately failed in that China eventually embraced capitalism, Russo contends that the Cultural Revolution remains important today, as it provides a resource for articulating an egalitarian politics. Examining four different phases of the Cultural Revolution, this book argues that we should view each phase as a confrontation between new political subjectivities imagined through the mass-experimentation of the Revolution, and the frameworks of political culture available to revolutionaries. The book is organized around the four phases Russo identifies in the ten-year span of the Cultural Revolution. Part 1 (chapters 1-3) explores what Russo calls the "historical-theatrical 'prologue' of 1965," and examines the controversy surrounding the historical drama Hai Rui Dismissed from Office, which Sandro interprets as a debate over the nature of historical materialism in understanding histories of Chinese peasant life. Part 2 (chapters 4-5) analyzes Mao's original intentions for the Cultural Revolution; chapter 4 focuses on Mao's anxieties about the destiny of socialism, while chapter 5 positions Mao's interventions between 1965-1966 as an attempt to remove obstacles to mass participation in the critical reexamination of revolutionary culture. Part 3 (chapter 6-8) focuses on the mass phase of the Cultural Revolution (1966-1968), and analyzes factional divides that led to organizational failure. Part 4 (chapters 9-10), examines the large mass study campaigns that took place from 1973-1976, and their attempt to reassess the events of the Revolution. These chapters also attend to the failure of these campaigns, and their halting by Deng Xiaoping, the head of government"--